Using agro-industrial waste (coco peat from coconut husk and rice hull) as alternative for exterior insulation and finish systems (EIFS) insulation board - Pingoy, Joshua Jake A. (2020)
Today, building design now shifts its focus into designing and building energy-efficient and sustainable structures. The goal is to utilize design methods and materials in order to improve quality of living for the inhabitants while being considerate about the natural environment. This research will focus on material development particularly on making a new insulating material out of agro-industrial waste specifically Rice Hull, and Coco Peat and then evaluate how effective the new material is for use as insulation. The study identified Coco Peat, and Rice Hull as the aggregate for the alternative EIFS insulation board. Throughout the research, the properties of the material such as Water-absorptive, flexural, compressive, thermal conductivity, and thermal resistance of the material were thoroughly explored through different tests. With the data obtained from performing the tests, results show that the alternative insulation boards with the formulation of an 18mm Compact Coco Peat with Urea Formaldehyde exhibits the strongest compressive strength capacity with 365 psi while the 18mm Compact Rice Hull with Urea Formaldehyde exhibits the strongest flexural strength capacity. Results from the hot box method also show that the alternative insulation boards have better thermal performance. The formulation with the lowest average temperature difference ratio was Coco Peat with Urea Formaldehyde with 0.0259 °C while the conventional polystyrene insulation board has an average of 0.1547 °C where the lower the temperature difference ratio, the better the material. With these results, the insulation boards made from agro- industrial waste namely coco peat and rice hull is a suitable alternative for the conventional EIFS polystyrene insulation board.